The Influence of Motivation and Tax Knowledge on Students' Career Interests in Taxation - Debi Masri; Muammar Rinaldi; Anton Eka Saputra (Outline Journal of Education, 2024)
This researchs aims to know The Effect of Motivation and Tax Knowledge on Career Interest in Taxation (Case study on Eka Prasetya Student Accounting Study Program) patially and simultaneously. The type of data used in this research is quantitative data. The data source used in this research are primary data. The population in this study was STIE Eka Prasetya Accounting Students Class of 2018-2021 is 226 respondents. The number of samples obtained is 69 respondents by using Slovin formula . The data were analyzed using multiple linear regression analysis method. T test show that motivation has no effect and is not significant on career interest in the taxation while Tax Knowledge has a significant and significant effect on career interest in the Taxation. F test show that Tax Motivation and Knowledge have a significant and significant effect on Career Interest in the Taxation. The results of the coefficient of determination test show that Career Interest in Taxation can be explained by Motivation and Tax Knowledge while the remaining is explained by other variables such as Perception, Professional Ethics, Career Perception, Gender, Self-Efficacy, and Labor Market Considerations.